2007
DOI: 10.1007/s12237-007-9024-5
|View full text |Cite
|
Sign up to set email alerts
|

A Dynamic Model of an Estuarine Invasion by a Non-Native Seagrass

Abstract: Mathematical and simulation models provide an excellent tool for examining and predicting biological invasions in time and space; however, traditional models do not incorporate dynamic rates of population growth, which limits their realism. We developed a spatially explicit simulation model that allows patch or population growth rate to change with population size through the incorporation of field data. We used the model to evaluate the invasion of a west coast estuary by the non-indigenous Japanese eelgrass,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 45 publications
1
3
0
Order By: Relevance
“…Based on our data and others (Nomme and Harrison 1991a;Bando 2006;Shafer et al 2007;Almasi and Eldridge 2008), it seems likely that Z. japonica thrives in the mid-intertidal zone of Willapa Bay because of its small size and high reproductive output, allowing it to spread quickly where abiotic conditions are variable and stressful, but competitive effects are low. Compared to introduced populations to the north and south, Z. japonica in Willapa Bay has the ''best of both worlds'': high sexual reproduction and germination from seed as in annual plants in British Columbia (Harrison 1982b), and over-winter persistence and effective asexual reproduction as in Yaquina Bay, Oregon (Kaldy 2006).…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…Based on our data and others (Nomme and Harrison 1991a;Bando 2006;Shafer et al 2007;Almasi and Eldridge 2008), it seems likely that Z. japonica thrives in the mid-intertidal zone of Willapa Bay because of its small size and high reproductive output, allowing it to spread quickly where abiotic conditions are variable and stressful, but competitive effects are low. Compared to introduced populations to the north and south, Z. japonica in Willapa Bay has the ''best of both worlds'': high sexual reproduction and germination from seed as in annual plants in British Columbia (Harrison 1982b), and over-winter persistence and effective asexual reproduction as in Yaquina Bay, Oregon (Kaldy 2006).…”
Section: Discussionsupporting
confidence: 63%
“…Unvegetated habitats can occur at suitable tidal elevations due to burrowing shrimp (Dumbauld andWyllie-Echeverria 2003, Almasi andEldridge 2008), and presence of shrimp in the unvegetated zone at NA may underlie the disjunct distributions of eelgrass congeners there. When burrowing shrimp were removed from this particular zone by application of carbaryl, Z. japonica rapidly (albeit temporarily, due to the small-scale experiment) expanded its distribution below ?0.55 m MLLW into the treated strips (Dumbauld 1994).…”
Section: Discussionmentioning
confidence: 99%
“…Harrison (1982) studied seasonal and annual variations of Z. japonica in lower British Columbia, Canada, and other studies of this species in PNW estuaries subsequently have been reported (below). In recent years a number of investigations of the occurrence and ecology of Z. japonica in Yaquina Estuary have been published , Larned 2003, Kaldy 2006, Almasi and Eldridge 2008, Young et al 2008, Shafer et al 2011, Kaldy and Shafer 2013.…”
Section: Zostera Japonica and Z Marinamentioning
confidence: 99%
“…Z. japonica recolonized 137 m 2 of a cleared 284 m 2 between April and October 2003, colonizing at a rate of approximately 25 m 2 per month (Schlosser et al, 2005). Colonization was also modeled for Yaquina Bay, and suggests that Z. japonica's most important limit to growth is vegetative shoot and seedling survival limited by competition (Almasi and Eldridge, 2008). In their model, Z. japonica grew rapidly for the first 20 years after initial invasion, followed by cycles around equilibrium.…”
Section: Gaps In Research For Informing Management Of Z Japonicamentioning
confidence: 99%